2018
DOI: 10.1016/j.chembiol.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of K-RAS4B by a Unique Mechanism of Action: Stabilizing Membrane-Dependent Occlusion of the Effector-Binding Site

Abstract: KRAS is frequently mutated in several of the most lethal types of cancer; however, the KRAS protein has proven a challenging drug target. K-RAS4B must be localized to the plasma membrane by prenylation to activate oncogenic signaling, thus we endeavored to target the protein-membrane interface with small-molecule compounds. While all reported lead compounds have low affinity for KRAS in solution, the potency of Cmpd2 was strongly enhanced when prenylated K-RAS4B is associated with a lipid bilayer. We have eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 33 publications
4
92
0
Order By: Relevance
“…Although it is long established that lipidated HVRs helps Ras GTPases anchor to the membrane, decades of research into the development of compounds that interfere with HVR lipidation, processing, and subsequent binding to membranes have failed to provide effective therapeutic reagents (70,71). Thus the binding interface between G-domain and membrane may provide a novel avenue to target K-Ras, as indeed has been very recently reported (63).…”
Section: K-ras Binding To Pip2mentioning
confidence: 55%
See 2 more Smart Citations
“…Although it is long established that lipidated HVRs helps Ras GTPases anchor to the membrane, decades of research into the development of compounds that interfere with HVR lipidation, processing, and subsequent binding to membranes have failed to provide effective therapeutic reagents (70,71). Thus the binding interface between G-domain and membrane may provide a novel avenue to target K-Ras, as indeed has been very recently reported (63).…”
Section: K-ras Binding To Pip2mentioning
confidence: 55%
“…In a simulation study, Prakash et al (40) reported the involvement of helices 3 and 4, and ␤-strands 1-3, as well as helix 2 on the opposite face of the catalytic domain in the K-Ras4B G12D interaction with POPS/POPC bilayers. More recently, the interaction of C terminally membrane-anchored K-Ras4B with PS was also studied experimentally by Ikura and colleagues (44,63) using nanodiscs. This study revealed two, if not possibly more, orientation states, but also suggested a GTPase nucleotide and effector-bound state-specific shift between these states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5B, 5E-5G). Previously described exposed and occluded orientations (38)(39)(40) are included in the α and β/β' states, respectively, and an experimentally-driven model of RAS-RAF association straddles the dividing line between the α and β states (39). HMM analysis indicates that direct transitions between β' and α are relatively rare (Fig.…”
Section: Lipid Dependence Of Ras Orientation and Competence For Effecmentioning
confidence: 99%
“…25 Their follow-up NMR study showed that this compound likely inhibits the function of K-Ras from the membrane surface. 26 Design of drugs that target the protein-membrane interactions is a relatively new idea. It this study, we propose a strategy of trapping K-Ras onto the membrane using membrane anchored cell penetrating peptides.…”
Section: Introductionmentioning
confidence: 99%